Knowledge, Expertise, and Committee Power in the Contemporary Congress. Issue 2 (30th October 2018) - Curry, James M.
Abstract : Scholars, practitioners, and observers typically portray committee influence as rooted in traditional congressional processes and practices, which are thought to provide committees with powerful opportunities to block and shape legislative proposals. The erosion of regular order processes suggests these traditional processes cannot underlie committee power in the contemporary Congress. Drawing on a mixed‐methods approach of interviews with congressional staff and an original data set of every amendment offered on the floor of the House of Representatives from 2005 to 2008, I find that absent these traditional process norms, committees in the contemporary Congress can rely on their specialized knowledge and expertise to influence the behavior of their colleagues and shape the legislation that passes.